Semangat Suporter Timnas Indonesia : Wujud Nasionalisme Di Arena Sepak Bola Dan Pengaruh Di Kancah Internasional - Dina Aulia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Football in Indonesia plays an important role in building national identity and spirit. This study examines the impact of Indonesian supporters' enthusiasm on nationalism at the global level. Supporters, often called the